Comparative Evaluation of Urinary Biomarkers BLCA1, BLCA4, 5-ALA, and HAL in Liquid Biopsy for Early Bladder Carcinoma Detection - Reddy, Shruti; Ghagane, Shridhar C; Nerli, Rajendra B (Asian Pacific Journal of Cancer Biology, 2026)
Introduction: Bladder cancer is associated with structural alterations in the cell nucleus. This study analyzed urine samples from patients with bladder cancer and healthy controls to assess nuclear matrix proteins (NMPs), specifically BLCA-1 and BLCA-4, which reflect tumor-related cellular changes. In addition, the study introduces a novel non-invasive liquid-biopsy approach using 5-aminolevulinic acid (5-ALA)-induced flow cytometry, alongside hexaminolevulinate (HAL)-induced flow cytometry and fluorescent cytology. Cancerous cells preferentially absorb these agents, leading to altered enzyme activity and intracellular accumulation of protoporphyrin IX (PPIX), which produces detectable red fluorescence in urine samples. Materials and Methods: The study involved 80 participants: 50 with confirmed bladder cancer (via imaging and histopathology) and 30 controls hospitalized for non-cancerous urological issues. Urine samples were collected in five 10 mL portions per participant. This initial study compared the diagnostic effectiveness of urine-based ELISA assays for BLCA-1 and BLCA-4 with 5-ALA-induced fluorescent cytology, HAL, and 5-ALA-induced flowcytometry. Results: The BLCA-1 showed 96% sensitivity and 90% specificity. While BLCA-4 demonstrated a sensitivity of 98% and a specificity of 93.3%, The 5-ALA-induced fluorescent cytology exhibited 93.3% sensitivity and 86.6% specificity. Both HAL and 5-ALA-induced flowcytometry achieved 80% sensitivity and specificity. The combined evaluation of BLCA-1 and BLCA-4 biomarkers demonstrated remarkable increase in sensitivity 97% and specificity 91.67 % respectively. Conclusion: The findings suggest that BLCA-1, BLCA-4, HAL, and 5-ALA are highly sensitive and specific non-invasive markers for bladder cancer detection, effectively distinguishing between high-grade and low-grade urothelial carcinoma. These marker panels could be integrated into routine screening protocols, potentially minimizing the need for invasive diagnostic procedures.